2008
DOI: 10.2478/v10038-008-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-Exercise Decrease in Handgrip Force Following a Single Training Session in Male and Female Climbers

Abstract: Purpose. The purpose of the study was to reveal a possible relationship between maximal gripping force and climbing ability as well as to compare a decrease in handgrip force caused by training session in male and female climbers. Basic procedures. Seventy-four climbers (49 males and 25 females) took part in a climbing session on artificial wall. Grip force of both hands was measured twicebefore and after the training session. Main findings. The subjects self-reported their climbing abilities in a quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A deeper understanding in the present study is that the error rate in the big and small finals, in which athletes compete for medals, is notably higher than that in the race of other final rounds on average error rate. A previous study showed that after a single climbing training, the strength of sport climbing athletes decreases [20]; in the final stages, the athlete performs one to four high-intensity workouts at high intensity, and the decline in strength can partly explain the increased rate of player errors. In addition, a current study reported that the psychological anxiety of elite athletes in the finals might be more significant than in other competition stages [13].…”
Section: Discussionmentioning
confidence: 99%
“…A deeper understanding in the present study is that the error rate in the big and small finals, in which athletes compete for medals, is notably higher than that in the race of other final rounds on average error rate. A previous study showed that after a single climbing training, the strength of sport climbing athletes decreases [20]; in the final stages, the athlete performs one to four high-intensity workouts at high intensity, and the decline in strength can partly explain the increased rate of player errors. In addition, a current study reported that the psychological anxiety of elite athletes in the finals might be more significant than in other competition stages [13].…”
Section: Discussionmentioning
confidence: 99%
“…Precisely, climbers get a 22% decrease in handgrip strength after lead climbing, indicating fatigue [36]. Supportively, Gajewski and Jarosiewicz [6] showed a decrease in handgrip strength in adult (male 27.4 ± 7.6 years, females 25.4 ± 7.2 years) climbers. In their research, female and male groups did not differ in climbing ability, while relative handgrip of females was significantly lower than male climbers.…”
Section: Discussionmentioning
confidence: 91%
“…Two studies have previously tested for and reported hand dominance effects in healthy climbers using hand grip dynamometers with reported differences of approximately 10%. 35,36 The hand grip dynamometers have been previously shown to be unable to differentiate between climbers and other athletes (which is why fingertip strength is considered a more appropriate measure of sport-specific strength). As the studies mentioned earlier did not use a climbing-specific test, this may explain the differences in our results.…”
Section: Discussionmentioning
confidence: 99%